EXTRA-CURRICULAR ENGAGEMENT IN RELATION TO ENGLISH PERFORMANCE OF THE EDUCATION STUDENTS OF COLEGIO DE LA PURISIMA CONCEPCION - Villorente, Ivie L. (President University, 2024)
Extracurricular activities have long been recognized as a valuable component of a well-rounded education, offering students opportunities to explore their interests, develop essential life skills, and enhance their overall well-being. These activities extend beyond the traditional classroom setting, providing a platform for students to engage in diverse pursuits ranging from sports and arts to community service and leadership roles. While the benefits of extracurricular involvement are widely acknowledged, their impact on academic performance, particularly in English language proficiency, remains a subject of ongoing research and debate. This research delved into the intricate relationship between extracurricular engagement and English performance of education students at Colegio de la Purisima Concepcion (CPC). Specifically, this study sought to find answer to the following: level of extra-curricular engagement of education students; level of English performance of the Education students; and to determine if there is a significant relationship between the extra-curricular engagement and the English performance of the Education students. This study adopted a quantitative-correlational research design. The participants of the study were the selected Education students from all-year levels under the College of Arts, Sciences, and Education (CASE) department of CPC. The simple random sampling was employed in the selection of the participants of the study. The total respondents were 82 students derived from using the Slovin’s formula. This study utilized a 20-item researcher’s made questionnaire to gather the data. The questionnaire was divided into two sections. Section A is composed of ten statements to describe the level of student’s extra – curricular engagement, and section B is composed of 10 statements to describe the level of student’s English performance. The panel of experts validated the questionnaire and it was tested for reliability before it was distributed to the respondents. The permission to conduct the study was secured from the College of Arts, Sciences and Education of Colegio de la Purisima Concepcion School administrators. The researchers distributed the questionnaire to the identified respondents and gave them time to answer the questions by checking the box that corresponds to their answers. Upon the retrieval of the research instruments, the data was then tallied and computer-processed using Statistical Package for Social Sciences (SPSS) software, analyzed and interpreted. Frequency count and percentage were used to find out the number of respondents that belonged to a particular category. The obtained mean scores were used to describe the extracurricular engagement and English performance of the students. Standard deviation was utilized to determine an indication of how far the individual responses to a question vary or